The Malayic-speaking; Orang Laut Dialects and directions for research - Anderbeck, Karl (Wacana, Journal of the Humanities of Indonesia, 2012)
Southeast Asia is home to many distinct groups of sea nomads, some of which are known collectively as Orang (Suku) Laut. Those located between Sumatra and the Malay Peninsula are all Malayic-speaking. Information about their speech is paltry and scattered; while starting points are provided in publications such as Skeat and Blagden (1906), K hler (1946a, b, 1960), Sopher (1977: 178-180), Kadir et al. (1986), Stokhof (1987), and Collins (1988, 1995), a comprehensive account and description of Malayic Sea Tribe lects has not been provided to date. This study brings together disparate sources, including a bit of original research, to sketch a unified linguistic picture and point the way for further investigation. While much is still unknown, this paper demonstrates relationships within and between individual Sea Tribe varieties and neighbouring canonical Malay lects. It is proposed that Sea Tribe lects can be assigned to four groupings: Kedah, Riau Islands, Duano, and Sekak.